2006
DOI: 10.1002/jemt.20370
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of CFP/YFP and GFP/mCherry pairs to donor photobleaching on FRET determination by fluorescence lifetime imaging microscopy in living cells

Abstract: Fluorescent protein-based FRET is a powerful method for visualizing protein-protein interactions and biochemical reactions in living cells. It can be difficult, however, to avoid photobleaching when observing fluorescent cells under the microscope, especially those expressing CFP. We compared the sensitivity of two protein-based FRET pairs to light-induced fluorescence changes in the donor, on FRET determination by fluorescence lifetime imaging microscopy (FLIM). Thanks to the very low excitation light levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
155
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(162 citation statements)
references
References 19 publications
7
155
0
Order By: Relevance
“…E is a monotonously decreasing function of the a factor [Eq. (15)], which itself depends linearly on e 2 , the ratio of the extinction coefficients of ECFP and EYFP at the donor excitation wavelength, 458 nm [Eqs. (12) and (13) (47)), e 2 cannot be determined unequivocally.…”
Section: Ratiometric and Acceptor Photobleaching Fret Results Obtainementioning
confidence: 99%
See 1 more Smart Citation
“…E is a monotonously decreasing function of the a factor [Eq. (15)], which itself depends linearly on e 2 , the ratio of the extinction coefficients of ECFP and EYFP at the donor excitation wavelength, 458 nm [Eqs. (12) and (13) (47)), e 2 cannot be determined unequivocally.…”
Section: Ratiometric and Acceptor Photobleaching Fret Results Obtainementioning
confidence: 99%
“…In case only a fraction of donors is in complex with an acceptor, the gained FRET efficiency can be considered as a lower limit of the real E value. To resolve donor subpopulations characterized by different E values, fluorescence lifetime measurements (15)(16)(17) or single molecule conditions are needed (18,19).…”
mentioning
confidence: 99%
“…Another frequently used combination is EGFP and the red fluorescent protein (RFP). Studies of proteins tagged with EGFP and monomeric RFP (mRFP) have already shown the potential use of this pair for FRET-FLIM applications (Peter et al 2005;Tramier et al 2006;Albertazzi et al 2009). …”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…due to tautomerisation, protonation or ion binding) mean that the fluorescence decay is often complex. Such dynamic complexity must be taken into consideration when extracting quantitative information from FRET measurements, and this is an emerging area of research [12][13][14][15][16].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%